Odpowiedź :
[tex]1. \\f(x)=(x-6)(x+3)\\f(x)=x^2+3x-6x-18\\f(x)=x^2-3x-18\\\Delta=(-3)^2-4*1*(-18)\\\Delta=9+72\\\Delta=80\\\sqrt{\Delta}=\sqrt{80}=\sqrt{4*4*5}=4\sqrt{5}\\x_1=\frac{-3-4\sqrt5}2=-\frac32-2\sqrt5\\x_2=\frac{-3+4\sqrt5}2=-\frac32+2\sqrt5[/tex]
2.
I sposob:
[tex]a) x^2-4=0\\\Delta=0^2-4*1*(-4)\\\Delta=0+16\\\Delta=16\\\sqrt{\Delta}=4\\x_1=\frac{-0-4}2=\frac{-4}2 = -2\\x_2=\frac{-0+4}2=\frac42=2[/tex]
II sposob:
b)
[tex]2x^2-16=0\\2x^2=16/:2\\x^2=8\\x_1=\sqrt{8}=\sqrt{4*2}=2\sqrt2 \text{ v } x_2 = -2\sqrt2[/tex]
[tex]c) \\4-100x^2=0\\4=100x^2 /:100\\\frac4{100}=x^2\\x_1=\sqrt{\frac4{100}}=\frac2{10}=\frac1{5} \text{ v } x_2=-\frac15[/tex]
3.
[tex]-x^2-5x-4<0\\\Delta=(-5)^2-4*(-1)*(-4)\\\Delta=25-16\\\Delta=9\\\sqrt{\Delta}=3\\x_1=\frac{5-3}{-2}=\frac{2}{-2}=-1\\x_2=\frac{5+3}{-2}=\frac8{-2}=-4\\a<0 \text{ - Ramiona paraboli skierowane w dol}\\\text{Rysujemy rysunek pomocniczy paraboli i odczytujemy x}\\\\x\in (-\infty; -4)\text{U}(-1; \infty)[/tex]